Structures of single, double and triple layers of lipids adsorbed on graphene: Insights from all-atom molecular dynamics simulations. (July 2017) - Rivel, Timothée; Yesylevskyy, Semen O.; Ramseyer, Christophe
Abstract: Non-covalent functionalization of graphene with phospholipids is a promising technique for biosensing applications and intracellular delivery of analytical probes and drugs. However, molecular details of the self-assembly of lipids on graphene surface is still poorly understood and hard to control. There is a clear lack of understanding of why various kinds of lipid aggregates can form on graphene. In the current work, we address this question by investigating equilibrium and dynamical properties of lipid layers adsorbed on graphene in water environment and in vacuum using all-atom Molecular Dynamics simulations. It is shown that a variety of lipid aggregates can form on top of graphene depending on initial orientation, number of adsorbed lipid layers and the presence of water. The lipid layers self-organize and reorient in order to minimize hydrophobic mismatch on graphene-lipid, lipid-lipid and water-lipid interfaces. Obtained structures range from homogeneous layers to the networks of inverted micelle-like structures and weakly bound cylindrical micelles on top of monolayers. Our results are in excellent agreement with recent experimental findings. Another pronounced effect of graphene is the strong ordering of the lipid atoms which are in direct contact with it. In all studied systems at least two well-structured atomic shells are formed above the graphene surface at the distances of 0.35 and 0.85 nm. Graphical abstract: